2011
DOI: 10.1145/2038617.2038627
|View full text |Cite
|
Sign up to set email alerts
|

Using Network Calculus to compute end-to-end delays in SpaceWire networks

Abstract: The SpaceWire network standard is promoted by the ESA and is scheduled to be used as the sole on-board network for future satellites. This network uses a wormhole routing mechanism that can lead to packet blocking in routers and consequently to variable end-to-end delays. As the network will be shared by real-time and non realtime traffic, network designers require a tool to check that temporal constraints are verified for all the critical messages.Network Calculus can be used for evaluating worstcase end-to-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…But Ferrandiz et al [2011] clearly showed with an illustrative example the flaws of the design and that such a modeling is pessimistic, leading to overdimensioning of resources. Ferrandiz et al [2011] consider a space wire network topology and introduced a special network element called the "wormhole section" to describe the wormhole routing with the network-calculus terminology.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…But Ferrandiz et al [2011] clearly showed with an illustrative example the flaws of the design and that such a modeling is pessimistic, leading to overdimensioning of resources. Ferrandiz et al [2011] consider a space wire network topology and introduced a special network element called the "wormhole section" to describe the wormhole routing with the network-calculus terminology.…”
Section: Related Workmentioning
confidence: 99%
“…But Ferrandiz et al [2011] clearly showed with an illustrative example the flaws of the design and that such a modeling is pessimistic, leading to overdimensioning of resources. Ferrandiz et al [2011] consider a space wire network topology and introduced a special network element called the "wormhole section" to describe the wormhole routing with the network-calculus terminology. This element envelopes a set of routers lying in the shared path between an analyzed flow and the blocking flow(s): the analyzed and the blocking flows enter the first router and exit through the last router of the wormhole section, with no additional blocking flows either entering or leaving from any other link within the wormhole section.…”
Section: Related Workmentioning
confidence: 99%
“…Several techniques have been proposed to provide an upper-bound on the worst-case delays of individual traffic flows [5,6,7,15], however, due to complex interference patterns, these methods yield pessimistic results [5].…”
Section: Related Workmentioning
confidence: 99%
“…Assuming that a packet is released at the critical instant t ∈ T , its worst-case traversal time Li(t) (expressed in absolute values) is computed by solving Equation 7.…”
Section: Worst-case Analysismentioning
confidence: 99%
“…Several methods have been proposed to obtain upper-bounds on worst-case latencies ( [8], [10], [11]), but they yield either pessimistic results [10], [11], or have complexity and scalability issues [8]. Conversely, if a platform contains multiple virtual channels ( [6], [7]), the benefits are twofold: (i) by avoiding idle routers, the performance of the wormhole switching technique is significantly improved ( [6], [7]) and (ii) preemptions can be implemented [24].…”
Section: Related Workmentioning
confidence: 99%